The concept of fraction of drug transported (ft) with special emphasis on BBB efflux of CNS and antiretroviral drugs. Issue 4 (13th February 2015) - Prasad, B; Unadkat, JD
<x xml:space="preserve">Abstract</x> The fraction of drug transported (ft) into or out of a tissue is a concept useful to understand the impact of transporters on absorption, distribution, metabolism, and excretion (ADME) and tissue distribution of a drug. Here, ft is utilized to explain the impact of transporters on central nervous system (CNS) distribution of drugs, drug interactions (DDI), and to predict the unbound brain concentration (Cu, b) of the drug. The latter is important to ascertain if Cu, b is sufficient for efficacy.